Investment Policy in the Conditions of the Knowledge Economy: New Tools and Valuable Bases - A. V. Kurochkin (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article is devoted to research of specific goals, objectives and content of the state investment policy in the conditions of formation and development of the knowledge-based economy. The authors analyze key features of the new economy, its influence to and interrelation with political, social and cultural spheres of society. Particular emphasis is placed on the need to develop a consensus strategy of the investment policy, the necessity of its inclusion in the broader context of national economic policy, taking into account a broad range of challenges and risks faced by modern society. The investment policy must be viewed in close connection with the rebranding of the area, its social, geographical and cultural characteristics. As key tools to solve this problem in the article describes modern network technologies: crowdsourcing, benchmarking, marketing territory, etc.